Degradabilidad ruminal in situ del pasto saboya (Panicum maximun) más la inclusión de varias concentraciones de cáscara de maracuyá (Passiflora edulis) - Arce Alcivar, Walter Enrique (2015)
The objective of this research was to evaluate in situ ruminal degradability of dry matter and organic matter Savoy grass (Panicum maximum) and agro-product of passion fruit peel (Passiflora edulis) and the inclusion of various levels of passion fruit peel. The treatments were: T1 Pasto Savoy; T2 passion fruit peel; Savoie T3 Pasto passion fruit peels 85% 15%; Savoie T4 Pasto passion fruit shell 75% 25%; T5 Pasto Savoy passion fruit peels 65% 35% 50% T6 Pasto Savoy passion fruit peel 50%. four fistulated animals were cannulated in rumen and used in this research design used a randomized complete block. The in situ degradability test was conducted in the laboratory of Rumiologia State Technical University of Quevedo, located in west longitude 79 ° 29 s and 01 ° South latitude 06 s. The site of the grass dry matter Savoie more various concentrations including passion fruit peel, degradability statistical differences existed between treatments at 0, 3, 6, 12, 24, 48 and 72 hours incubation in the rumen in situ, statistically the best treatment was the shell of passion due to its high content of digestible carbohydrates, but also can be seen that treatment 6 (Pasto Savoy 50% more shell maracuyá 50%) have better percentages of degradability as compared to other treatments , this is because the soluble carbohydrates help increase Savoie pasture in situ degradability. In situ ruminal degradability of organic matter pasture Savoy's inclusion peel passion there is statistical difference between treatments (p <0.05), behaving with the best average of degradability shell Passion fruit because of its high carbohydrate content available and thus have a higher degradability, and this is reflected in the treatment 6 (Pasto Savoy 50% more passion fruit peel 50%), since high percentages of passion fruit peel increase ruminal degradability in situ pasture Savoy.